Ataxia and dysarthria due to an ABCA2 variant: Extension of the phenotypic spectrum. (July 2019) - Aslam, Faiza; Naz, Sadaf
Abstract: Introduction: Ataxias are heterogeneous disorders that are caused by variants in a large number of genes. The study was conducted to identify the molecular basis of a movement disorder in a consanguineous Pakistani family. Methods: We performed clinical assessments and magnetic resonance imaging of the older of two siblings affected with a movement disorder. Molecular analyses included whole-exome sequencing in order to delineate the underlying pathology of the disorder. Segregation of variants with the phenotype was checked by Sanger sequencing. Results: Symptoms of the two affected subjects were consistent with cerebellar ataxia with dysarthria. Magnetic resonance imaging did not reveal brain abnormalities. The levels of low density lipid proteins were elevated in blood samples of both affected individuals. Whole-exome sequencing data analyses identified a frameshift variant, c.4993delG:p.(Val1665TyrfsTer36) in ABCA2 (NM_212533.2) which segregated with the disorder and was absent from all publicly available databases and ethnically matched controls. Although recessively inherited ABCA2 variants have been reported in two patients who had intellectual disability with global developmental delays, our study demonstrates the role of an ABCA2 variant in the pathogenesis of ataxia with dysarthria. The phenotype observed in our patients shows high concordance with that observed in Abca2 knockout mice. Conclusion: Our research links an ABCA2 variant with a distinct form of ataxia with dysarthria in humans and demonstrates pleiotropic effects due to the gene mutation. The findings further delineate the importance of low density lipid metabolism and intracellular sterol trafficking in brain function. Highlights: Ataxias are heterogeneous neurological disorders. We analyzed two affected siblings who had a movement disorder. We identified a frameshift variant of ABCA2 and correlated it with ataxia and dysarthria. Our work, together with previous reports, demonstrates that ABCA2 variants cause pleiotropic defects in humans.